De koorafscheiding in Engeland - Steensma, Regnerus (Jaarboek voor liturgieonderzoek, 2002)
By the end of the Middle Ages, virtually every church in England had a choir or rood screen, and more than a thousand have been preserved. The primary function of the screen was to emphasise the division between the nave and the chancel. This function is the same as that of the cross-wall with arcade, which it will have partially replaced. In addition, it also often served as the support for the triumphal cross, the rood, as well as for the gallery, the loft. The vast majority of the screens in England and Wales date from the fifteenth and sixteenth centuries. The designs of the screens reveal regional differences, particularly between East Anglia and Devon. Many of the screens have painted panels. The representations are usually of angels. Evangelists, Apostles and saints. In various English churches there is a gallery or loft at the border between chancel and nave, usually constructed above a screen, although examples are also known without a screen. The main function of the loft was to provide a place for a choir and for individual musicians, both vocal and instrumental. During the Reformation in the sixteenth century, many lofts were dismantled because they were too strongly associated with Catholic worship, and above all with the crucifixion group (rood), which definitely had to go.